A quantum correction based on Schrodinger equation applied to Monte Carlo device simulation. - Winstead, B. (IEEE Transactions on electron devices)
A full-band Monte Carlo model has been coupled to a Schrodinger equation solver to account for the size quantization effects that occur at heterojunctions, such as the oxide interface in MOS devices. The overall model retains the features of the well-developed semi-classical approach, by treating self-consistently the Schrodinger solution as a correction to the particle-based Monte Carlo. The simulator has been benchmarked by comparing results for MOS capacitors and double gate structures with a self-consistent quantum solution, showing that the proposed approach is efficient and accurate. This quantum correction methodology is extended to device simulation, by accounting for the interplay between confinement and transport through a parameter which we call "transverse" temperature. This approach appears to be valid even for nanometer-scale devices in which nonequilibrium ballistic transport is occurring. We present simulations of a 25-nm MOSFET and compare results obtained with and without the quantum correction.